The level of happiness as a determinant of sustainable development - Sas, Nataliia (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
The happiness index is not taken into account among the components of the measurement system for quantitative and qualitative assessment of sustainable development. The article substantiates the possibility of using the happiness index as a determinant of sustainable development. The author suggests that achieving happiness is the ultimate goal of controlled social, economic and political systems, and the level of happiness can be used to measure the level of sustainable development. To compare the dynamics and outline the direction of movement, the subjective component of happiness index is decomposed as follows: stress, life values of individuals and life satisfaction. The author proposes to consider the needs of end users of sustainable development depending on the views on content of happiness. According to the author, the generalized classification of the archetypes of happiness is as follows: hedonism, eudaimonia, rat race, nihilism, subjective well-being. These typologies of happiness and their carriers do not exclude the necessity to meet the needs as devised by Maslow, however, they significantly expand the range of attention of public authorities and state policy regarding their variability. In terms of marketing, different archetypes of happiness and their representatives are different customer groups, meeting the needs of which allows to better solve the problem (achieving happiness) of user, enterprise, organization and society as a whole. The author believes that further research consists in studying the needs (primary and secondary, absolute and relative, higher and lower, positive and negative, general and special, urgent, private, individual and group, etc.) and developing an assortment matrix of services for each archetype; research of existing experience and development of practical ways of using available resources to ensure the opportunity for next generations to be happy; development of conscious attitude to the fact that natural resources are common to all living things on the planet and that all creatures great and small also require meeting their needs (in their diversity); creation of an appropriate scientific and practical platform for bringing together like-minded people – representatives of different areas of activity.